2012
DOI: 10.3109/07853890.2011.590521
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid sensitivity in inflammatory bowel disease

Abstract: Glucocorticoid therapy is used in the treatment of moderate to severe inflammatory bowel disease (IBD). However, IBD patients display varying degrees of glucocorticoid sensitivity: some respond rapidly to the given treatment, whereas others show no response, or develop steroid therapy-related side-effects. At present, we cannot foresee whether the patient will benefit from the administered glucocorticoids or not. During the past 10 years, numerous attempts have been made to provide the means to identify and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 73 publications
2
17
0
1
Order By: Relevance
“…Glucocorticoid strongly suppresses COX-2 expression induced by inflammatory stimuli and has been used in the treatment of many hypoxia-occurred pathological states (Baschant et al 2012;Reuter et al 2012;Sidoroff and Kolho 2012). We have recently reported that dexamethasone represses both hypoxia-induced COX-2 and induction of GILZ is a key event in hypoxia-induced COX-2 inhibition by glucocorticoids (Lim et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Glucocorticoid strongly suppresses COX-2 expression induced by inflammatory stimuli and has been used in the treatment of many hypoxia-occurred pathological states (Baschant et al 2012;Reuter et al 2012;Sidoroff and Kolho 2012). We have recently reported that dexamethasone represses both hypoxia-induced COX-2 and induction of GILZ is a key event in hypoxia-induced COX-2 inhibition by glucocorticoids (Lim et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…In paediatric patients the therapy is commenced with 1-2 mg/kg/day of prednisone equivalents (max 60 mg) and tapered off preferably during 10 weeks [6]. However, glucocorticoid dependency affects approximately 20-40% of the patients and prolonged steroid courses are often seen in clinical practice [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…GCs play a critical role in the treatment of inflammatory bowel disease (IBD), including both ulcerative colitis (UC) and Crohn's Disease (CD), where they are used to induce remission in patients with moderate to severe disease 1, 2 . Although GCs have a long history of use, many patients do not adequately respond to treatment 3-5 and require alternative medical therapies and/or surgery. A prospective cohort study following CD patients through a course of the synthetic GC prednisolone found that 20% of patients were GC resistant (no regression of symptoms) and 59% of patients required surgery within 1 month of initiating GC therapy 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In one study the rate of GC resistance in severe disease (42%) was only slightly larger than that in moderate disease (35%) 14 . Few, if any, predictors of clinical response to GCs exist in IBD 5 . Biomarkers that could identify GC response in patients before treatment would improve IBD management.…”
Section: Introductionmentioning
confidence: 99%